The Practice of Exclusive Breastfeeding among Mother in Bulili Public Health Center of Palu City, Indonesia - Fadjriah, Rasyika Nurul; Salamah, Ummu; Jafar, Nurhaedar; Nur, Rosmala; Kurnia, Dwei; Bohari (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to analyze the factor which influence the practice of giving exclusive breastmilk on toddler mothers at Bulili Community Health Center. The research method used was quantitative method with cross sectional approach. The population in this research were all mothers who had kids age 7-24 months and 75 samples were selected through purposive stratified random sampling. The research results show that mothers with exclusive breastmilk were 35 respondents (46,7%), mothers who were not exclusive breastmilk 40 respondents (53,3%). The result of bivariate analysis shows that there is significant correlation between knowledge level (p= 0,000), job (p=0,046), family support (p=0,000), support from medical staff (p=0,002), promotion of formula milk (p=0,000), and parity (p=0,008) towards the practice of giving exclusive breastmilk. The dominant factor of exclusive breastfeeding failure is low family support, mothers’ low knowledge about exclusive breastmilk, and strengthened by the reason of busy working until exclusive breastfeeding is replaced by formula milk. The implication of this research is that breastmilk support community is necessary to give social support to mothers and families, minimize the promotion of formula milk, and increase the education about exclusive breastmilk to the mothers.